Applied Aspect Of Shodhan Chikitsa In Psoriasis (Ekakustha) - Kumar, Ravindra; Sharma, Ashu; Kumari, Sujata; Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2021)
Psoriasis is a chronic inflammatory disease of skin which is non-infectious in origin. It is characterized by erythematous plaques (of well defined margins) with silvery scale on extensor surface and scalp. This disease not only affects patient’s physical appearance but also disturbs the mental and social health, as the lesions appears externally which are embarrassing. In Ayurveda the disease Ekakushtha resembles more with the characteristics of psoriasis. Ekakustha is described as Vata-Kaphaj disease. The exact aetiology of this disease is unknown but it is believe that there are many factors(like genetic, dietary, immunological and psychological)which helps in precipitation of this disorder. There is no treatment available for complete cure of Psoriasis. The use of various drugs such as corticosteroids, anthalin, psoralen and ultraviolet rays is recommended by modern science. which supress the immune system (if used for long time) and have negative impact on body. In Ayurveda repeated Shodhan Chikitsa (Purificatory processes) and Shaman Yogas (Pacifying) are mentioned in treatment of Kushtha (Skin diseases) . Shodhan Chikitsa (Purificatory processes) is able to give satisfactory results in Ekakustha and also used for prevention of many disorders and promotion of healthy life.A lot of work has already been done for psoriasis keeping Vaman Karma (emesis) and Virechan Karma (purgation) as the main procedures, In the present work there is a new approach towards use of Basti karma will also discussed along with these two, as the Vatadosha is suggested to be a main Dosha (among all three Doshas) in creating the pathogenesis of psoriasis. The combined effect of all the three procedures was found very effective and clinically safe as no adverse drug reactions were reported during treatment period.